Modulation and bioinformatics screening of hepatic mRNA-lncRNAs (HML) network associated with insulin resistance in prediabetic and exercised mice. - Kazeminasab, Fatemeh; Marandi, Sayed Mohammad; Baharlooie, Maryam; Nasr-Esfahani, Mohammad Hossein; Ghaedi, Kamran (Nutrition & Metabolism, 2021)
Background: Insulin resistance is associated with prediabetes and further progression to type 2 diabetes mellitus (T2DM). This study aims to investigate novel hepatic lncRNAs associated with key genes in insulin resistance in prediabetes. Methods: In the bioinformatics phase, we have collected screened a pool of lncRNAs and mRNAs according to their potential association to prediabetic condition. We performed pathway analysis of mRNAs, using DAVID tool based on KEGG repository data. Then, we used Python programming language to get a subset of lncRNAs located in 50 kb proximity with high-fat (HF)-responsive mRNAs. In the experimental phase, prediabetic mice model was established by the treatment of HF diets for 12 weeks. After this treatment, HF-fed animals were divided into two groups of endurance exercised or sedentary, both continuing on the HF diet for 8 weeks. Besides, a group of diabetic mice was treated using a HF diet for 8 weeks followed by injection with STZ solution and then a HF diet for another 4 weeks. Results: We found three genes having paired lncRNAs annotated in insulin resistance pathway. Their hepatic expression levels were altered in prediabetic condition as upregulation of Srebf1 was associated with GM38501, upregulation of Pck1 was associated with Ctcflos and GM36691, downregulation of Cpt1b was associated with GM44502. All of these expression patterns were replicated in diabetic mice, correlated positively with their predicted lncRNAs. Interestingly, exercise reversed their expression patterns. Conclusions: We suggest that the expression pattern of the hepatic mRNA-lncRNA (HML) network in prediabetic state undergoes similar modification to that of diabetes.